Interventional knowledge, attitude and practice study of standard precautions among health care workers at a tertiary care hospital in Western India (Panacea Journal of Medical Sciences, 2023)
Background: Standard precautions are the backbone of any efficient infection control program. Compliance with standard precautions has been a major challenge for health care workers, especially in developing countries.Aim: To access the impact of the training program on health care workers (HCW) knowledge, attitude, and practice towards standard precautions.Materials and Methods: We conducted an interventional Knowledge, Attitude, and Practice (KAP) study among 150 HCW (50 Doctors, 50 Nurses, and 50 Technicians) in a tertiary care hospital from June 2019 to December 2019. We carried out educational interventions through training sessions with pre- and post-test questionnaires. We compared pre and post questionnaire mean scores to access the impact of short educational videos and seminars on HCWs using unpaired t-tests.